Famous women personalities - Vinita (Chennai : Sura Books, 2004)
Content. -- Mother Teresa. -- Florence Nightingale. -- Annie Besant. -- Helen Keller. -- Maria Montessori. -- Indira Gandhi. -- Marie Curie.
Keywords: Women -- Biography